1998
DOI: 10.1093/ndt/13.3.723
|View full text |Cite
|
Sign up to set email alerts
|

Combined heart-kidney transplantation: report on six cases

Abstract: Combined heart-kidney transplantation from the same donor should be proposed to patients who would qualify for transplantation of each organ within a few years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 0 publications
1
11
0
2
Order By: Relevance
“…We found that recipients of SHK transplants had substantially lower rates of acute cardiac rejection and acute renal rejection at 1-year posttransplant compared to their respective comparator groups. The cardiac acute rejection rate at 1 year in SHK was 14.5% in our study that agrees with earlier studies (3,4) and the rate of renal acute rejection was less than 7%, despite no zero-mismatch transplants in this group. This is in keeping with suggestions in previous studies that partial graft tolerance in simultaneous multiorgan transplantation may lead to a decrease in the acute rejection rate compared to single organ transplants.…”
Section: Lower Acute Rejection Rates In Shksupporting
confidence: 93%
“…We found that recipients of SHK transplants had substantially lower rates of acute cardiac rejection and acute renal rejection at 1-year posttransplant compared to their respective comparator groups. The cardiac acute rejection rate at 1 year in SHK was 14.5% in our study that agrees with earlier studies (3,4) and the rate of renal acute rejection was less than 7%, despite no zero-mismatch transplants in this group. This is in keeping with suggestions in previous studies that partial graft tolerance in simultaneous multiorgan transplantation may lead to a decrease in the acute rejection rate compared to single organ transplants.…”
Section: Lower Acute Rejection Rates In Shksupporting
confidence: 93%
“…Patient outcomes of HKT appear similar to HTA. 4,5,[13][14][15][16] Although still marginal, HKT is increasingly performed despite the lack of good evidence regarding patient selection.…”
Section: Discussionmentioning
confidence: 99%
“…El trasplante renal diferido no presenta diferencias respecto del trasplante renal en un paciente sin trasplante cardíaco ya que se hace en un paciente estable y de la forma habitual y con los criterios de selección habituales, si bien la inmunosupresión que se utiliza es la del cardíaco 10 . En los casos simultáneos, si bien la técnica quirúrgica del trasplante renal es la misma, se hace en un paciente en peor situación clínica lo que conlleva una mayor mortalidad peroperatoria que puede llegar hasta un 21% 3,7,8,15 ; en estos casos de trasplante simultáneo los criterios de selección del donante se basan fundamentalmente en la compatibilidad ABO y una prueba cruzada negativa sin tener en cuenta la compatibilidad HLA 4, 13,[15][16][17] ; además se benefician de un tiempo menor de isquemia fría, que al igual que en nuestros casos está en torno a las 6 horas 4,12,15 .…”
Section: Discussionunclassified
“…Este fenómeno de protección frente al rechazo podría resultar de la inmunomodulación del receptor por el trasplante simultáneo o por la introducción de elementos hematopoyéticos 19 . En las diferentes series entre el 62 y 100% de los pacientes con trasplante simultáneo cardio-renal no tuvieron episodios de rechazo agudo 2,3,13,14,16 . Narula 8 en su registro multicéntrico encuentra que en el 48% de los casos no hubo rechazo, 27% le tuvo solo en el corazón, el 14% solo en el riñón y el 11% en los dos, concluyendo que el rechazo cardíaco es menor en los trasplantes combinados que en el aislado.…”
Section: Discussionunclassified